Winning and Losing in Investor–State Dispute Settlement. (26th February 2019) - Samples, Tim R
Abstract : As tensions between investors' rights and sovereign power escalate, investor–state dispute settlement (ISDS) has become a focal point of backlash and controversy. As a result, ISDS now embodies two opposing currents in international law: (1) the erosion of sovereignty that accompanied economic globalization, trade frameworks, and investment treaties following the Second World War and (2) more recently, reassertions of sovereignty prompted by recent backlashes against the global economic order. This article measures and evaluates outcomes of the ISDS system for sovereign participants. Using the best available data, this article contributes more detailed assessments of sovereign winners (home states of claimants) and sovereign losers (respondent states) in the ISDS system. This article also considers the distribution and the proportional impact of outcomes for sovereign participants, both of which are fundamental in the legitimacy debates surrounding the ISDS system.